Enhancing antimicrobial properties of glass ionomer cement through metallic agent reinforcement: A systematic review and meta-analysis - Danelon, Marcelle; Nunes, Gabriel Pereira [UNESP]; Sterzenbach, Torsten; Hannig, Christian (Elsevier, 2025)
OBJECTIVES: This systematic review and meta-analysis (SRM) aimed to assess the impact of incorporating metallic agents into glass ionomer cement (GIC) and resin-modified glass ionomer cement (RMGIC) on their microbiological properties and antibacterial activity. DATA SOURCES: Following PRISMA guidelines, the SRM included studies published up to August 21, 2024. STUDY SELECTION: The eligibility criteria included clinical trials, in situ, and in vitro studies. The data were analyzed using RevMan software, and bias risk was assessed with the Joanna Briggs Institute's Checklist for in vitro studies and the ROBINS-I tool for clinical trials. RESULTS: Out of 2,393 screened records, 32 studies were included. Results showed that metallic agents like silver, zinc oxide, titanium dioxide, and copper enhanced the antimicrobial properties of GIC and RMGIC. Most studies reported superior antimicrobial effects compared to controls, with only two studies showing neutral effects. Meta-analysis revealed that GIC with 5 % TiO₂ or 2 % ZnO nanoparticles significantly reduced S. mutans viability, while silver zeolite at 1 % and 5 % concentrations showed strong effects. Similarly, adding silver or ZnO to RMGIC improved its activity against S. mutans and L. acidophilus. The studies showed a low risk of bias. CONCLUSIONS: Metallic agents enhance the antimicrobial efficacy of GIC/RMGIC, offering a promising solution for biofilm control in dental restorations. However, further research is needed to optimize their clinical application, particularly through in vivo studies, and to assess their impact on mechanical, esthetic, and cytotoxic properties. CLINICAL RELEVANCE: Incorporating metallic agents into GIC and RMGIC enhances their antibacterial properties, improving biofilm control in dental restorations. This modification may reduce the risk of secondary caries and prolong restoration longevity.